670 Learning Curve Associated With Thoracoscopic Anterior Vertebral Body Tether for Idiopathic Scoliosis: Analysis of Three Independent Surgeons. (April 2023) - Lau, Darryl; Kurland, David B.; Neifert, Sean N.; Wei-Hung Hwang, Steven; Pahys, Josh; Samdani, Amer F.
Abstract : INTRODUCTION: Anterior vertebral body tethering (VBT) is a fusionless surgery that harnesses growth to correct idiopathic scoliosis. More surgeons are beginning to implement VBT. METHODS: A single-institution retrospective review of three surgeons' experiences of their first 40 single thoracic VBT and 20 double thoracolumbar VBT cases was performed. Patients had skeletally-immature, idiopathic scoliosis and underwent thoracoscopic VBT. Primary outcomes were intraoperative measures and radiographic correction. A pooled and individual surgeon analysis was performed with multivariable modeling. RESULTS: A total of 126 single and 60 double VBT patients were included. Mean age was 12.7 years and 13.4% were male. Mean segments tethered was 8.8 in single and 11.0 in double VBT. Mean preoperative thoracic scoliosis was 50.6°: single (49.3°) and double (53.3°). Mean lumbar scoliosis was 35.9°: single (20.9°) and double (49.0°) (p < 0.001). Average OR time was 273.7 minutes with double VBT taking significantly longer (216.4 vs. 394.0 minutes, p<0.001). Mean blood loss was 194.5 ml and fluoroscopy dose 73.6 mGy with no differences between single and double VBT. For single VBT, there was a significant decrease in operative time per 10 cases performed (287.9 to 174.1. minutes). This trend was present for all surgeons. A nonsignificant decrease in fluoroscopy dosing was evident (70.1 to 53.5 mGy, p=0.154). Single and double VBT achieved 41.1% and 47.3% thoracic curve correction, respectively. Double VBT achieved 51.5% lumbar curve correction. Increased experience was not associated with absolute or percentage curve correction for single and double VBT. CONCLUSIONS: VBT is an exciting fusionless surgical option for scoliosis. Increased experience resulted in shorter operative time but curve correction was adequate even at the start of the learning curve. Additional studies of long-term results of initial case experiences are needed.